(untitled) (CIPEEX, 2025)
This study analyzes jurisdiction for prosecuting and adjudicating latrocínio (robbery resulting in death) in Brazilian criminal procedure and explains why, despite the lethal outcome, it does not fall within the Jury’s purview. It is a doctrinal and case-law review that examines the legal classification of latrocínio as a property crime aggravated by result and the constitutional confinement of the Jury’s competence to intentional crimes against life. The aim is to set out the normative grounds and judicial criteria used to assign the case to a single-judge court and to assess the procedural consequences of adjudication by an incompetent body. The method consisted of analyzing provisions of the Penal Code and Code of Criminal Procedure, in dialogue with scholarship and precedents, highlighting the distinction between intentional homicide and the complex offense that primarily protects property. The findings indicate that the death element in latrocínio does not transfer jurisdiction to the Jury, because it is not an intentional crime against life; moreover, improper submission to the Jury entails absolute lack of jurisdiction, nullifying the trial and requiring remand to the competent court. It concludes that correctly identifying the legally protected interest and the typicity of latrocínio prevents nullities, ensures respect for the natural judge, and promotes coherence in penal responses.